Exploring patients’ perceptions and experiences of treatments for the prevention of variceal bleeding: a qualitative study - Dhiraj Tripathi; Jonathan Mathers; Chris Poyner (BMJ Open Gastroenterology)
Background The most common fatal complication of liver cirrhosis is haemorrhaging caused by variceal rupture. The prevention of the first variceal bleed is, therefore, an important clinical goal. Little is known about patients’ experience of treatments geared towards this, or of their perceptions of treatments prior to being exposed to them.Aims To explore the factors impacting patient preference for, and actual experience of carvedilol and variceal band ligation.Methods Semistructured interviews were conducted with 30 patients from across the UK at baseline, prior to random allocation to either carvedilol or variceal band ligation. Twenty patients were interviewed a second time at 6-month follow-up. Five patients who declined the trial were also interviewed. Data were analysed using thematic analysis.Results There was no clear preference for either treatment pathway at baseline. Key factors reported by patients to influence their treatment preference included: negative experiences with key treatment processes; how long-term or short-term treatment was perceived to be; treatment misconceptions; concerns around polypharmacy and worries around treatment adherence. Patient treatment experience was influenced by their perceptions of treatment effectiveness; clinical surveillance; clinician interaction and communication, or lack thereof. Carvedilol-specific experience was also influenced by the manifestation of side effects and patient dosage routine. Variceal band ligation-specific experience was positively influenced by the use of sedation, and negatively influenced by the procedure recovery period.Conclusions These data do not support a view that the patient experience of beta-blockade for prevention of variceal bleeds is likely to be superior to variceal band ligation.